Insignificant Effects of Coloring and Labeling on Memory Span and Serial Recall - Saleh, Noora N.; Huffer, Michael D. (Iraqi Journal of Science, 2020)
Human perception involves many cognitive processes, such as memory, attention, and critical thinking. An important cognitive process is memory, which is usually connected with the storing and retrieval of information. Different colors and labeling have diverse physiological effects on humans. Our investigation aimed to determine if a change in color or labeling would have a significant effect on memory span and serial recall. However, our results do not support that coloring and labeling have significant impacts on a subject’s memory.